Regulation of Nicotiana benthamiana cell death induced by citrus chlorotic dwarf-associated virus-RepA protein by WRKY 1 - Qin, Yangyang; Zhao, Jinfa; Wang, Jiajun; Ye, Xiao; Zhou, Changyong; Zhou, Yan (Frontiers in Plant Science, 2023)
Abstract Citrus chlorotic dwarf-associated virus (CCDaV), a Citlodavirus species in the family Geminiviridae, causes tremendous economic loss to the citrus industry in China. Some proteins encoded by geminiviruses are crucial for the interaction between virus and host plant. However, the exact functions of CCDaV-encoded proteins such as CCDaV-RepA have not been investigated. In this study, we first present evidence that CCDaV-RepA elicits a hypersensitive response (HR) in Nicotiana benthamiana, accompanied by the production of H2O2 and ion leakage. These results suggest that CCDaV-RepA is a potential recognition target for inducing host defense responses. Notably, CCDaV-RepA is located in the nucleus, and the nuclear localization ability of CCDaV-RepA was found to be related to the induced HR response in N. benthamiana. Silencing experiments revealed that HR-like cell death induced by RepA was markedly inhibited in WRKY1-silenced N. benthamiana. Moreover, the expression level of WRKY1 was upregulated in RepA-GFP infiltrated N. benthamiana.